Cutis 2020
DOI: 10.12788/cutis.0052
|View full text |Cite
|
Sign up to set email alerts
|

Severe Phymatous Rosacea of the Nose, Cheeks, and Chin Treated With Hydrosurgery

Abstract: Phymatous rosacea is a rare and severe form of rosacea that manifests as disfiguring soft-tissue hypertrophy and sebaceous gland hyperplasia and fibrosis. Most cases are surgically treated; surgical modalities vary, however, ranging from cryosurgery to conventional excision, and consensus guidelines for surgical management do not exist. The Versajet II Hydrosurgery System (Smith-Nephew) is a highpressure, pulsatile lavage system. We present the case of a 75-yearold man with severe phymatous rosacea of the nose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Eine sehr schöne dermatologische Indikation ist auch das Abtragen eines Rhinophyms und Gnatophyms. Dabei wird das kürzere 8 mm-Handstück mit 45°-Neigung eingesetzt [9,10].…”
Section: Introductionunclassified
“…Eine sehr schöne dermatologische Indikation ist auch das Abtragen eines Rhinophyms und Gnatophyms. Dabei wird das kürzere 8 mm-Handstück mit 45°-Neigung eingesetzt [9,10].…”
Section: Introductionunclassified
“…For example, in a study of axillary osmidrosis (n=93), hydrosurgery showed improved patient satisfaction and fewer postoperative complications compared to traditional surgery [ 3 ]. Case reports of severe phymatous rosacea, which currently lacks standard surgical guidelines, document successful treatment with hydrosurgery [ 4 ]. Additionally, hydrosurgery can safely and rapidly debride various ulcer types in outpatient settings [ 5 ].…”
mentioning
confidence: 99%